THE EFFECT OF USING ENGLISH SONG TOWARDS STUDENTS’ SPEAKING SKILL AT THE VIII GRADE OF SMPI NURUL HIKMAH II BEKASI - Yasir, Muhamad; Reknosari, -; Susilawati, - (STKIP PGRI Tulungagung, 2025)
The purpose of this research is to find out whether there is an effect of using English song towards students’ speaking skill at the VIII grade of SMPI Nurul Hikmah II Bekasi. The population in this research is 26 students by taking 20 students as a sample. The research method use the Pre-Experimental Desain One Group Pre-Test Post-test. The researcher use Oral test with the criteria of assessment are Pronunciation, Grammar, Fluency, Vocabulary and Content, with 1 question. The score of Pre Test are mean = 49.9, Median = 54.39, Mode = 57.265, Variant = 178.36, and Standard Deviation = 13..35. It means that the students in the pre test has been unsatisfactory yet. While the Post test are mean = 77.95, Median = 83.48, Mode = 87.12, Variant = 176.78, and Standard Deviation = 13.29, It means that the students in the post test has had a good score. With Data analysis technique using . obtained 4.42 next to compare in with standard of a significant (α = 0.05 which is dk = n-1 = 19 ) = 1.72, hence, 4.42 1.72 it means that is refused whereas is accepted, it can be concluded that there is an effect of using English song towards students’ speaking skill at the VIII grade of SMPI Nurul Hikmah II Bekasi.